Chemical Composition and Biological Properties of Colostrum and Milk Fed to Calves - O‘rinov, H. S.; Kuldoshev, O. U.; Ubaydullayeva, G.B.; Eshimov, D. (American Journal of Bioscience and Clinical Integrity, 2026)
This study investigates the chemical composition and biological properties of colostrum and milk fed to calves under farm conditions. Special attention was given to the dynamics of mineral components, particularly total calcium and inorganic phosphorus, during different stages of lactation. Milk and colostrum samples were collected at various post-calving periods and analyzed using standard biochemical methods. The results showed that the concentration of essential minerals gradually decreased as lactation progressed, which may negatively influence metabolic processes, skeletal development, and natural resistance in calves. Calcium and phosphorus deficiencies during early growth stages can lead to impaired physiological development and increased susceptibility to metabolic disorders. The findings highlight the importance of monitoring milk quality and implementing timely nutritional correction through balanced feeding and mineral supplementation of lactating cows. Ensuring adequate mineral and vitamin content in milk contributes to improved calf health, growth performance, and efficient utilization of genetic potential, thereby enhancing overall productivity in cattle farming systems.